Chronic Liver Disease (CLD) - An Indian Knowledge System Review (AYUSHDHARA, 2025)
India has two recognized systems of medicine: Ayurveda and Allopathy. There is also a system of healing in the form of Yog, breathing exercises, postures and meditation that has been in use since 3000 BCE is practiced. Non-communicable diseases have become prevalent in modern India due to unhealthy dietary habits and lifestyle changes. Alcoholic and non- alcoholic liver disease is caused by excessive alcohol consumption, uncontrolled dietary and behavioural regimen over a long period of time. Ingested alcohol and other pathological factor alters metabolism, producing acetaldehyde and damaging the liver. First, liver cells become clogged with fatty droplets, leading to liver inflammation called hepatitis. Subsequent excessive consumption of unplanned diet and irregular lifestyle leads to cirrhosis. In this disease some liver cells die and then abnormal regeneration occurs, resulting in the formation of multiple nodules and extensive fibrosis. These disease leads to poor liver function followed by body wasting and ascites. Treatment through Indian Knowledge System like Ayurvedic medicine and Panchakarma procedure gives better effect and better results. Use of hepato protectors, liver stimulants and Rasayana medicines. Choalaganges, Tikta, Madhura Rasayukta medicines, Mootral medicines and protein supplements have proven to be effective in treating liver disease. The one most important protocol to treat liver disease is the miraculous procedure called Panchakarma (bio-purification) plays magical role to mange liver disease. This article will focus on the role of Indian Knowledge System in treating liver disease.